Marginalities of the Handwritten Qurans of Highland Dagestan as a Historical Source - M. N. Osmanova (Научный диалог)
The article is devoted to the study of the content of extra-textual records — marginals — in the margins of handwritten Qurans, recorded by Dagestan oriental scholars at different times while working with written monuments in private and mosque book collections of highland Dagestan. It was established that most of the discovered marginals were made in Arabic, however, since the beginning of the 18th century, such records were often kept in local languages using Arabic script. It is shown that the Quran, due to its sacred functions, became a repository of the most important documents of various nature. It is reported that extra-textual recordings are extremely diverse in their content, they affect many aspects of the socio-political, spiritual, economic and cultural life of the region. The experience of studying marginals over the past several decades is summarized. The author of the article draws attention to the newest findings of the Qurans made by archaeographic expeditions in 2017—2019 in private book collections in the Shamil region of the Republic of Dagestan. It is emphasized that an analysis of their thematic composition and a scientific description of the manuscripts stored in them will give an idea of some aspects of the social, cultural and religious life of the peoples of Dagestan.